Facial discoid lupus erythematosus complicated by a Candida tropicalis fungal granuloma in a patient with rhupus syndrome: a case report of successful treatment with oral itraconazole - Lingling Dong; Ting Zhang; Tong Hua; Yan Wang; Zhenhua Nie; Qingkang Lyu; Zuotao Zhao (Frontiers in Medicine, 2026)
Discoid lupus erythematosus (DLE) is a chronic cutaneous subtype of lupus erythematosus characterized by inflammatory lesions that are highly susceptible to secondary infection, particularly in immunocompromised individuals. Cutaneous fungal granulomas caused by Candida tropicalis and superimposed on pre-existing DLE lesions are exceedingly rare and pose substantial diagnostic challenges. We report the case of a 48-year-old female patient with a 2-year history of rheumatoid arthritis (RA), who presented with facial lupus lesions in January 2024. During her disease course, she met the classification criteria for systemic lupus erythematosus (SLE), leading to a diagnosis of rhupus syndrome (RA-SLE overlap). After eight months of treatment with hydroxychloroquine and prednisone, her cutaneous lesions showed no improvement and instead progressed to nodules and pustules. Histopathological examination of a skin biopsy revealed classic features of DLE accompanied by granulomatous inflammatory infiltrates. Periodic acid–Schiff (PAS) staining and subsequent fungal culture confirmed C. tropicalis as the causative pathogen. The patient was ultimately diagnosed with DLE complicated by secondary C. tropicalis fungal granuloma in the setting of Rhupus syndrome. She received a 3-month course of combination therapy consisting of oral itraconazole (200 mg once daily) plus topical naftifine-ketoconazole cream, which resulted in complete clearance of all facial lesions. No recurrence was observed throughout a 12-month post-treatment follow-up period.